Improving Balance in Older Adults Through Gaze Stability Exercise: A Community-Based Physiotherapy Program - Widiarti, Afrianti Wahyu; Ghufroni, Afif (Poltekkes Kemenkes Surakarta, 2026)
Background: The elderly population continues to grow with increased life expectancy, but healthcare services remain insufficient. As a result, many older adults face balance disorders and a higher risk of falls, worsened by limited access to physiotherapy. This community service program aims to train elderly people in efforts to improve their knowledge and skills in managing fall risks using gaze stability exercises taught by physiotherapists. Methods: Participants’ understanding of age-related balance problems improved markedly, with correct responses increasing from 18.3% pre-education to 86.7% post-intervention (a 68.4-point improvement). All participants successfully performed the main gaze stability exercises, although some needed assistance with vergencies. They also reported greater confidence during standing and walking and showed strong motivation to continue the exercises independently at home. Results: Participants’ understanding of age-related balance problems improved substantially, with the average level of correct responses increasing from 18.3% before the education session to 86.7% after the intervention, representing an average improvement of 68.4 percentage points. In addition, all participants were able to perform the main gaze stability exercise components correctly, although several required assistances with vergence movements. Participants reported increased confidence during standing and walking activities and expressed strong motivation to continue the exercises independently at home. Conclusion: Gaze stability exercise education is a feasible and beneficial community-based physiotherapy approach to enhance balance awareness, confidence, and self-management among older adults. The program is recommended for routine implementation in elderly community health services with support from physiotherapists and local health cadres.